2018
DOI: 10.1007/978-981-10-8456-0_2
|View full text |Cite
|
Sign up to set email alerts
|

A Structural View of Negative-Sense RNA Virus Nucleocapsid Protein and Its Functions Beyond

Abstract: Negative-sense single-stranded RNA virus (NSRV) is featured by their ribonucleoprotein (RNP) complex composed by viral polymerase and genomic RNA enwrapped by nucleocapsid protein (NP). The RNP is packaged in virions and plays a central role throughout virus lifecycle. In the past decade, structural biology presents molecular insights into NPs encoded by most representative NSRVs, helping to understand the mechanism of RNP formation. Interestingly, works initiated from structural biology also reveal unexpected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Using peptide mass fingerprinting analysis, ORF I-encoded peptides were also identified in the virion crude extract of SsNSRV-1. The prediction of secondary structure demonstrated that ORF I contained many helix, one coiled coil, two DNA-binding sites (76-83, 227-237), and one protein binding region [50]. The morphology of the particles of SsNSRV-1 was previously observed by transmission electron microscopy (TEM): filamentous, 25-50 nm in diameter,~1000 nm in length.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Using peptide mass fingerprinting analysis, ORF I-encoded peptides were also identified in the virion crude extract of SsNSRV-1. The prediction of secondary structure demonstrated that ORF I contained many helix, one coiled coil, two DNA-binding sites (76-83, 227-237), and one protein binding region [50]. The morphology of the particles of SsNSRV-1 was previously observed by transmission electron microscopy (TEM): filamentous, 25-50 nm in diameter,~1000 nm in length.…”
Section: Discussionmentioning
confidence: 86%
“…In a canonical virus NP structural family of NSRV, N-and C-lobes were mainly formed by a set of α-helices. N-and C-extensions were constituted by loop and/or α-helix [49,50]. In previous study, ORF II was proved as a N protein without significant similarity with other viruses in Mononegavirales by SDS-PAGE protein electrophoresis analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Although this flow of biological information is universal in all living things, viruses have evolved ways to rewrite these dynamics in some cases avoid the need for a DNA intermediate at all. One of the more unique strategies for replacing DNA as the long-term storage of information derives from that of negative-sense RNA viruses that maintain their genomes in an antisense orientation bound by viral nucleoprotein (NP) and the RNA-dependent RNA polymerase (RdRp) (Lou, 2018).…”
Section: Introductionmentioning
confidence: 99%